2016
DOI: 10.1111/mmi.13492
|View full text |Cite
|
Sign up to set email alerts
|

The TamB ortholog of Borrelia burgdorferi interacts with the β‐barrel assembly machine (BAM) complex protein BamA

Abstract: Summary Two outer membrane protein (OMP) transport systems in diderm bacteria assist in assembly and export of OMPs. These two systems are the β-barrel assembly machine (BAM) complex and the translocation and assembly module (TAM). The BAM complex consists of the OMP component BamA along with several outer membrane associated proteins. The TAM also consists of an OMP, designated TamA, and a single inner membrane (IM) protein, TamB. Together TamA and TamB aid in the secretion of virulence-associated OMPs. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 103 publications
(196 reference statements)
1
45
0
Order By: Relevance
“…More recently, in Borrelia burgdorferi , the TamB component of TAM was shown to interact directly with BamA and to be an essential component of the BAM complex 73 . Exactly how the BAM and TAM systems communicate with one another, how they decide their substrates, and what mechanistic role each may have in OMP biogenesis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in Borrelia burgdorferi , the TamB component of TAM was shown to interact directly with BamA and to be an essential component of the BAM complex 73 . Exactly how the BAM and TAM systems communicate with one another, how they decide their substrates, and what mechanistic role each may have in OMP biogenesis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence point to a similar exclusion mechanism at the second checkpoint in the OM, where periplasmic lipoproteins are blocked from "flipping" through the OM due to assumption of their final tertiary structure (57, 76, 92-94). The B. burgdorferi BAM protein BamA was shown to be at least indirectly involved in this process (134), and it remains to be determined if/how the other identified B. burgdorferi BAM complex proteins (56, 114), including the IM protein TamB (135), play a role in lipoprotein secretion. Recent work has shown that some Neisseria surface lipoproteins are secreted to the surface through the lumen of beta-barrel integral OM proteins (44), but homologs are missing from Borrelia genomes.…”
Section: Discussionmentioning
confidence: 99%
“…TamA is found throughout the Proteobacteria , and TamB has an even broader distribution through Gram‐negative bacterial lineages (Heinz et al ., ). Recent studies with Borrelia burgdorferi suggest that in organisms that lack a TamA, TamB interacts instead with BamA (Iqbal et al ., ; Stubenrauch et al ., ). Phylogenetic analyses suggested a model wherein the TAM evolved originally from a complex of BamA and TamB, with a subsequent gene duplication of bamA giving rise to a second Omp85 sequence in the genome, ultimately evolving to become TamA (Heinz et al ., ).…”
Section: Introductionmentioning
confidence: 99%